Who decides about the city - decision making in local self-governments - Savkić, Danijela J (Arhitektura i urbanizam, 2016)
The main research topic in this paper is the problem of decision-making within the institution of local development in Serbia. Analysis of the interaction of actors and normes, rules and regula, including the interest of local development, contributes to understanding of the complexity of decision-making on local development, and key actors that influence effectiveness and efficiency of the spatial interventions. The research is conducted within the process of local development, in which the guidelines and rules of urban plans are translated into concrete interventions.